2020
DOI: 10.1051/parasite/2020057
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection among women of childbearing age in an endemic region of Romania, 2016–2018

Abstract: Toxoplasmosis is an important worldwide zoonosis caused by the protozoan parasite Toxoplasma gondii. This parasitic infection is often asymptomatic in immunocompetent people. However, if the infection occurs in pregnant women, it can have serious consequences for the foetus. In this study, we evaluated the seroprevalence of T. gondii in women of childbearing age in Arad County, Western Romania. Serum samples from 2626 women were analysed using a Siemens ADVIA Centaur XP Immunoassay System. Toxoplasma gondii Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Our results revealed a high prevalence of T. gondii IgG antibodies in patients diagnosed with schizophrenia, organic (personality and behaviour) disorders, and mental disorders concerning alcohol abuse, compared with controls. Similar to the results of other studies conducted in this region [4,13], the prevalence of T. gondii antibodies tended to increase with age in both groups: psychiatric patients and controls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results revealed a high prevalence of T. gondii IgG antibodies in patients diagnosed with schizophrenia, organic (personality and behaviour) disorders, and mental disorders concerning alcohol abuse, compared with controls. Similar to the results of other studies conducted in this region [4,13], the prevalence of T. gondii antibodies tended to increase with age in both groups: psychiatric patients and controls.…”
Section: Discussionsupporting
confidence: 88%
“…T. gondii seroprevalence differs widely between countries [1][2][3]. Humans can be infected by ingestion or handling of undercooked or raw meat, ingestion of contaminated food or water [2,4], organ transplantation, via blood or leucocytes, or vertically from the acutely infected pregnant women to the foetus [2,5]. In immunocompetent subjects, the postnatally acquired T. gondii infection is generally considered clinically insignificant [3].…”
Section: Introductionmentioning
confidence: 99%
“…The seroprevalence of IgG antibodies generally increased with age, as showed by Olariu et al [ 62 ], higher in women aged over 40 years (71.4%) compared with young women under 20 years of age (33.3%). This difference was confirmed by studies performed 7 years later [ 54 ] and 12 years later in the Banat region by Motoi et al and Mihu et al, respectively [ 59 , 63 , 64 ]. The estimated annual infection risk associated with age showed high susceptibility from childhood to adolescence (3–4.5% annual infection risk), a stable level for adults (1–2%), and then an increase up to 5.5% for individuals over 65 years old [ 53 ].…”
Section: Resultsmentioning
confidence: 57%
“…The seroprevalence was higher in rural areas (70%) compared with urban areas (48.1%). The Banat region had different seroprevalence rates, with a study conducted in 2015 showing a rate of 55.55% [ 54 ] in women of childbearing age, while other studies conducted in 2020 and later found rates between 38.81% and 55.8% [ 58 , 59 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation